Personality disorder functioning styles and empathy in trainee nurses: the mediating and moderating roles of death attitudes - Pan, Jianing; Wu, Haozhen; Wang, Yujie; Zhang, Bingren (Frontiers in Psychiatry, 2025)
BackgroundThere is abundant evidence that an individual’s personality traits may influence their level of empathy. However, the role of death attitudes in the relationship between personality disorder functioning styles of nurses and their empathy remains to be elucidated.MethodsPersonality disorder functioning styles, death attitudes, and empathy levels were assessed in 614 Chinese trainee nurses using the Parker Personality Measure (PERM), the Death Attitude Scale-Revised (DAP-R), and the Jefferson Scale of Empathy-Health Professionals (JSE-HP).ResultsAmong the trainee nurses, DAP-R Fear of Death, Death Avoidance, Escape Acceptance, Approach Acceptance, and Neutral Acceptance(-) partially mediated the negative correlations between all PERM styles except Obsessive-compulsive style and empathy. Furthermore, DAP-R Fear of Death, Escape Acceptance, and Approach Acceptance fully mediated that between Obsessive-compulsive style and empathy. Fear of Death and Death Avoidance attenuated empathy among those with higher Narcissistic and Dependent styles, respectively.ConclusionDeath attitudes served as a mediator and moderator in the relationships between personality disorder functioning styles and empathy among trainee nurses, suggesting the need for targeted death education among early-career nurses with personality dysfunctions.